Discrimination and multicultural identity configurations: The mediating role of stress. (November 2016) - Yampolsky, Maya A.; Amiot, Catherine E.
Abstract: The present research examines perceived discrimination as a predictor of how multicultural individuals negotiate and configure their different cultural identities within the self. We focused on three multicultural identity configurations: having one predominant identity (categorization), compartmentalizing one's different identities, and integrating one's identities. Since discrimination is related to intraindividual discordance and is stressful, we examined the mediating role of stress in the associations between discrimination and the identity configurations in 259 multicultural individuals. Mediation analyses revealed that greater discrimination predicted compartmentalization through greater stress, while lower discrimination predicted greater identity integration through lower stress. Categorization was not predicted by discrimination or by stress. Discrimination and stress appear to have damaging and depleting roles that hamper multiculturals' capacity to reconcile their identities into a cohesive whole.